First Record of Mint Leaf Beetle, Chrysolina herbacea (Duftschmid, 1825), (Coleoptera: Chrysomelidae) in Iraq (Baghdad Science Journal, 2019)
The insect is diagnosed and named by the National Center of Biotechnology Information (NCBI), USA as the Mint leaf Beetle Chrysolina herbacea alnadawi (Duftschmid, 1825), (Coleoptera: Chrysomelidae). The diagnosis was performed depending on the DNA analysis by 73% similarity with Chrysolina herbacea (Duftschmid, 1825) sequence, In the present study. It is recorded as a new insect pest on mint plant Mentha puleguim (L,1753) (Lamiaceae). DNA analysis confirmend that it is recorded for the first time in Iraq and the Arab world as well as the Middle East. Those insects were observed initially during August 2017 in residential gardens of Al-Bonooq district in Baghdad / Iraq.